Diagnostic and Planning Value of T2-Weighted and Flair MRI for Radiotherapy Target Contouring in Brain Tumors - Rafiq Sulistyo Nugroho; Fadlan Adima Adrianta; Suaydiy Okdiyanzah; Sakena Nurza; Aisyah Amalia (Asian Journal of Health Research, 2026)
Introduction: Brain and central nervous system tumors, particularly gliomas, represent a growing global burden with poor prognosis. Radiotherapy post–maximal resection is central to management, yet its success depends on precise target delineation to preserve healthy tissue. MRI, especially T2-weighted and FLAIR sequences, is standard for planning, but the optimal sequence remains unclear.    Material and Methods: A systematic review was conducted according to PRISMA guidelines. Literature searches were performed in PubMed, ScienceDirect, and EuropePMC databases up to 25 May 2025. Observational or comparative studies assessing T2-weighted and/or FLAIR MRI for radiotherapy target contouring were included. Study selection, data extraction, and quality assessment using ROBINS-I were independently performed by two reviewers.    Results: From 246 identified studies, four studies met the inclusion criteria. Overall, FLAIR-based delineation consistently produced larger clinical and planning target volumes compared with T2-weighted imaging, capturing additional regions of peritumoral abnormality. Recurrence pattern analyses suggested that FLAIR-defined volumes may better encompass infiltrative tumor margins. High interobserver agreement was reported for MRI-based target delineation, supporting the feasibility of MRI-only workflows, although selective CT integration remained important for certain organs at risk.    Conclusion: Although the evidence is limited, both T2-weighted and FLAIR MRI sequences play an important role in brain tumor radiotherapy planning. While T2-weighted imaging generates more conservative target volumes, FLAIR sequences better capture infiltrative edema, potentially lowering recurrence risks at the cost of increased healthy tissue irradiation. Careful, consensus-driven sequences selection is required to balance tumor coverage and normal tissue sparing.